Controllable assembly of CeO2 micro/nanospheres with adjustable size and their application in Cr(VI) adsorption. (March 2016) - Sun, Jiajia; Wang, Chengrui; Zeng, Li; Xu, Pengfei; Yang, Xiaodan; Chen, Jun; Xing, Xianran; Jin, Quan; Yu, Ranbo
Graphical abstract: Highlights: Controllable assembled CeO2 micro/nanospheres have been simply synthesized. Size control is realized by adjusting stirring-time before hydrothermal process. The CeO2 micro/nanospheres show high specific surface area up to 182 m 2  g −1 . The CeO2 micro/nanospheres exhibit superior performance in Cr(VI) adsorption. Abstract: CeO2 micro/nanospheres with perfect spherical morphology, large specific surface area, high porosity, high stability and adjustable diameter were hydrothermally synthesized from a simple system, and the stirring-time before hydrothermal process was found to be the key factor for the final particle size control. The CeO2 spheres with diameters from ∼800 nm to ∼50 nm could be harvested by controllable synthesis. And the highest specific surface area of these CeO2 spheres could achieve 182 m 2  g −1 . Moreover, CeO2 spheres with higher specific surface areas (182 m 2  g −1 and 117 m 2  g −1 ) showed excellent performance in removal of heavy metal ion Cr(VI) from the aqueous solution. The Cr(VI) removal efficiencies could reach up to 94%.